West Nile virus T-cell ligand sequences shared with other flaviviruses: a multitude of variant sequences as potential altered peptide ligands. - Jung, K; Khan, A; Tan, B; Hu, Y; Simon, G; Nascimento, E; Lemonnier, F; Brusic, V; Miotto, O; Tan, T; Marques, E; Dhalia, R; et al. (2012)
Phylogenetic relatedness and cocirculation of several major human pathogen flaviviruses are recognized as a possible cause of deleterious immune responses to mixed infection or immunization and call for a greater understanding of the inter-Flavivirus protein homologies. This study focused on the identification of human leukocyte antigen (HLA)-restricted West Nile virus (WNV) T-cell ligands and characterization of their distribution in reported sequence data of WNV and other flaviviruses. H-2-deficient mice transgenic for either A2, A24, B7, DR2, DR3, or DR4 HLA alleles were immunized with overlapping peptides of the WNV proteome, and peptide-specific T-cell activation was measured by gamma interferon (IFN-γ) enzyme-linked immunosorbent spot (ELISpot) assays. Approximately 30% (137) of the WNV proteome peptides were identified as HLA-restricted T-cell ligands. The majority of these ligands were conserved in ∼≥88% of analyzed WNV sequences. Notably, only 51 were WNV specific, and the remaining 86, chiefly of E, NS3, and NS5, shared an identity of nine or more consecutive amino acids with sequences of 64 other flaviviruses, including several major human pathogens. Many of the shared ligands had an incidence of >50% in the analyzed sequences of one or more of six major flaviviruses. The multitude of WNV sequences shared with other flaviviruses as interspecies variants highlights the possible hazard of defective T-cell activation by altered peptide ligands in the event of dual exposure to WNV and other flaviviruses, by either infection or immunization. The data suggest the possible preferred use of sequences that are pathogen specific with minimum interspecies sequence homology for the design of Flavivirus vaccines.